Eine Welt der Ordnungen Weltpolitische Ordnungsformen des 20. und 21. Jahrhunderts - Senn, Martin; Kraxberger, Andreas M. (innsbruck university press, 2022)
This edited book offers an overview of different forms of order in 20th- and 21st-century world politics. After a general discussion of the concept of (political) order, the book discusses seven forms of order on a regional and global level, ranging from anarchic forms of order like the (automatic) balance of power to increasingly hierarchical forms of order like hegemony, empire and the world state. The book was written by students of the Masters Program in Political Science at the University of Innsbruck and is intended to be an introduction to forms and theories of order in world politics.